Pengaruh Store Atmosphere, Kualitas Pelayanan dan Visual Merchandising Terhadap Keputusan Pembelian: Studi Pada Pelanggan Mr. K Cafe BSB City Semarang - Imam Gozali (Dharma Ekonomi, 2024)
As time goes by, the combination of store atmosphere, service quality and visual merchandising has become an important factor for cafe business owners and customers in choosing a place to gather and chat over coffee. This research aims to analyze the influence of store atmosphere, service quality and visual merchandising on purchasing decisions for Mr. customers. K cafe BSB City Semarang. The population in this study were all customers who visited using a non-random sampling technique, totaling 96 respondents using accidental sampling. As for collecting data by distributing questionnaires to respondents who happen to be found. The results of the analysis show that store atmosphere and service quality have a positive and significant effect on purchasing decisions, while visual merchandising has a negative and insignificant effect on purchasing decisions.